Influence of Parameters of Cold Isostatic Pressing on TiO2 Films for Flexible Dye-Sensitized Solar Cells. (21st July 2011) - Peng, Yong; Liu, Jefferson Zhe; Wang, Kun; Cheng, Yi-Bing
Abstract : Cold Isostatic Pressing (CIP) is used to make TiO2 working electrodes for flexible dye-sensitized solar cells (DSCs). Different CIP processes, varying pressures from 50 MPa to 200 MPa and holding time 1 s up to 600 s, are performed to study the effect of CIP on the resistivity of TiO2 electrode thin films and the power conversion efficiency (PCE) of DSCs. The results show that the CIP process has significantly improved the PCE of DSC devices. Electrochemical impedance spectroscopy (EIS) analysis indicates a clear correlation between the PCE enhancement and the resistivity reduction in TiO2 thin films after various CIP processes. Porosity reduction and localized joints formed between some TiO2 nanoparticles due to the friction heat in the CIP process are believed to be responsible for the resistivity reduction of the TiO2 working electrode thin films.